Integrating Scenario‐Based and Component Reading Skill Measures to Understand the Reading Behavior of Struggling Readers. Issue 1 (February 2014) - Sabatini, John P.; O'Reilly, Tenaha; Halderman, Laura K.; Bruce, Kelly
<x xml:space="preserve">Abstract</x> In recent years, researchers, educators, and policy makers have called for a new generation of reading comprehension assessments (e.g., Partnership for 21st Century Skills, 2008). Advocates of this movement argue for a deeper type of reading assessment, one that captures students' ability to not only understand single texts in isolation but also to engage in purposeful, multisource integration of sources. While this shift in how we define and measure reading comprehension is laudable, assessments must also measure the fundamental reading skills that may impede higher‐level comprehension processes. This article presents data from two assessments that were designed to work in tandem to provide a more complete picture of reading comprehension. Middle school students were given a component skills battery which measured core reading skills such as word recognition, decoding, vocabulary, and morphology, as well a second assessment designed to measure reading comprehension. Reading comprehension was measured using a scenario‐based assessment approach, which required students to read a range of sources to fulfill a particular reading goal. The results indicate that students, including struggling readers, were able to read, understand, and problem solve in complex learning environments, but students' ability to do so was often tempered by their basic reading skills. We argue that including a measure of component skills alongside a measure of higher‐level comprehension is beneficial in interpreting student performance. Accordingly, we present the results on the scenario‐based measure as a function of reading component skills and argue for the value of using this approach for struggling readers.